Combination of kinetic maceration - digestion in the extraction of areca seeds (Areca catechu L.) - Nur L. Rahmah; Beauty S.D. Dewanti; Fitrotul Azizah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
Pinang (Areca catechu L.) is one of the plantation commodities from the Palmae group. One of the secondary metabolites contained in areca nut is tannin. Tannins are easily soluble in aquadest so extraction using aquadest solvents is the right choice. Extraction with kinetic maceration method with solvents of distilled water combined with digestion is an effective way to increase extract yield and have a fairly small operational risk. Therefore, in this study studied variations in temperature and extraction time using a combination method of kinetic maceration - digestion of the quality of tannins produced. The experimental design in this study consisted of two factors: the first factor was the extraction temperature with three levels, namely 40;60 and 80 oC and the second factor was extraction time with five levels, namely 4, 6, 8, 10 and 12 hours. The combination of kinetic maceration - the right digestion on yield and quality of areca nut tannin extract (crude areca nut tannin) was obtained at 40 oC with extraction time of 4 hours with a yield value of 12.20% (dry basic), moisture content of 0.023%, tannin content of 424.99 mg GAE / g. (dry basis) and IC50 42.54 ppm.